Cortical oscillations in tinnitus - Holding, Martin (2018)
Tinnitus, described as a phantom perception of sound in its absence is a condition that affects millions of people worldwide. In its chronic form it can be associated with increased levels of anxiety and depression and can be highly debilitating in extreme cases. It is commonly held that it is related to deficits in hearing, either as a result of ageing or due to noise exposure. However beyond this there is little else known about the precise mechanisms involved in its generation or maintenance. In particular, little is known about the neural properties of tinnitus. Neural oscillations of various frequencies have been linked to tinnitus, although the evidence for which specific frequencies are involved is somewhat mixed. The main aim of the present thesis was to investigate these neural oscillations further, both in how they relate to the perception of tinnitus and how they can potentially be modulated.